Pemantapan Profesi Keguruan (P2k) Kegiatan Profesi Keguruan - Nabilah Luthfiyyah; Wahyuddin Wahyuddin; Jamaluddin Ariffin (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Education is crucial for human resources in Indonesia; factors such as inequality of teaching staff, lack of facilities and budget affect the quality of education. Creative teachers in learning methods determine success. The PBL approach in sociology in high school is considered relevant, despite challenges such as lack of social interaction and motivation to learn. Research at SMAN 8 Mandai focuses on implementing PBL using the PTK method in two cycles, involving PBL learning innovation with exploration, elaboration and confirmation stages. Evaluation uses observation, tests and interviews. The results show significant improvement in cycle II, reaching the level of learning completeness. In conclusion, PBL is effective in improving the quality of sociology learning in class XI IPS 1 SMAN 8 Mandai.